Rehabilitation With Mandibular Implant-Retained Complete Overdenture Using the Association of Two Retention Systems - de Souza Batista, Victor Eduardo; de Souza Batista, Fábio Roberto; Vechiato-Filho, Aljomar José; Lemos, Cleidiel Aparecido De Araújo; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP] (Wolters Kluwer, 2016)
ABSTRACT: This article reports a case of oral rehabilitation with two-implant-retained mandibular overdenture using bar/clip and ball attachment bilaterally on the distal side. A patient aged 69 years, fully edentulous, presented herself to private practice complaining about the instability of mandibular denture. Several possibilities of rehabilitation with advantages and disadvantages were explained to the patient, based in the clinical and radiograph examinations, and patient desire, in which she opted by conventional maxillary complete denture and two-implant-retained mandibular overdenture. Two external hexagon implants of 3.75?×?10 mm were placed in anterior area of mandible. The fabrication of the metal framework with bar/clip and ball attachment bilaterally on the distal side was planned based on prior arrangement of the artificial teeth. Internal adaptation and occlusal adjustments were performed in the day of insertion of finalized denture and instructions about maintenance and sanitation. The patient showed satisfaction with the final result of her treatment, and no complications were observed during this period. The association of bar/clip with ball system may be viable as option of retention for mandibular implant-retained complete overdenture; however, further randomized controlled trials are necessary to obtain detailed knowledge about the topic.